Elective Surgery for Diverticulitis in Swiss Hospitals - Faes, Seraina; Hübner, Martin; Demartines, Nicolas; Hahnloser, Dieter; Martin, David; , The Swiss Snapshot Diverticulitis Group; Abitabile, Paolo; Abrazhda, Dritan; Arigoni, Michele; Bakhshi-Tahami, Vahid; Barras, Jean-Pierre; Beck, Thomas; et al. (Frontiers in Surgery, 2021)
Objective: To assess current management of diverticulitis in Switzerland. Methods: Prospective observational study of diverticulitis management and outcomes in surgical departments over a 3-month time period. Hospital category was graded according to the Swiss Medical Association (FMH) as: U: University; A: Cantonal; B: Regional; P: Private. Results: 75 participating hospitals treated 1015 patients, among whom 214 patients (21%) had elective sigmoid resections in 49 hospitals. Indication for elective resection were recurrent diverticulitis, previous complicated diverticulitis, fistulas, and stenosis. Surgeries were performed completely laparoscopically in 185 cases (86%) and required conversion to open in 19 cases (9%). Overall postoperative complication rate was 18% (n=39) and no mortality was observed. Operation time, surgeons experience and hospital stay differed considerably between hospital categories. Conclusions: Elective sigmoid resection for diverticulitis in Switzerland was mainly performed laparoscopically with low postoperative morbidity. Different practices and outcomes between institutions were observed.